Peran Gereja untuk Mendidik Jemaat dalam Pengelolaan Sampah di GMIM Nazareth Tingkulu Kota Manado - Virjily A. Nelwan; Benny Binilang; Heldy J. Rogahang (Peneliti.net, 2021)
The purpose of this research is to find out how the role of the Church in waste management in Tingkulu Village, Manado City. This research is a research that uses qualitative methods and the research is conducted in Tingkulu Village, Manado City in 2020. Data collected through observation, interviews and documentation study. From the results of the analysis and interpretation of the data, it is indicated that 1). The environment in Kelurahan Tingkulu is still dirty. 2). Congregation members' awareness of environmental cleanliness is still lacking. 3). So far, the role of the Church has only been in the form of appeals and directions to congregation members to always keep the environment clean and always throw garbage in the space provided. 4). There is no special program run by the Church regarding the handling of the waste problem. From these findings, it is recommended for the Church to pay more attention to the condition of the environment which is increasingly damaged and the damage is caused by irresponsible human activity. It is time for the Church together with all its members to carry out activities that are beneficial for themselves and for the environment, so that one day it can be passed on to our children and grandchildren later.